(untitled) (Revista Nacional de Odontología, 2017)
Introduction: This study aims to analyse the oral health status and its related factors in edentulous patients using conventional total dentures that assisted to the Faculty of Dentistry of the University of Antioquia. Methods: A descriptive study was conducted in 111 adults treated in the period 2009-2016. A survey and clinical examination was performed compiling information about socio-demographic information, medical history, oral hygiene, TMJ and dentures status, use, and satisfaction and evaluation of the quality of life related to oral health (OHRQOL). Analysis of the variables by absolute and relative frequencies by sex was carried out. Results: Most of the study population (98.2%) live in low and middle-income neighbourhoods. 82.9% of patients presented basic studies. More than half of the population (69.4%) reported having a good self-perceived health, however it was found that 53.2% reported suffering hypertension, diabetes 23.4%. ¾ of assessed patients reported cleaned both upper and lower oral mucosa (higher in women, 83.8%). The most frequent characteristics found in both dental prostheses in descending order were pigmentations, dental calculus and porosities. The population surveyed expressed greater satisfaction with the upper denture compared to the lower one. It was found that more than three quarters of the population studied have a low OHRQOL. Conclusions: Strategies that contribute to improving the quality of oral health care are required by means of follow-up activities to the treatments carried out in in this group.